DEVELOPMENT OF A CENTER FOR THE ACCOUNTING TRANSACTION COSTS OF THE ENTERPRISE - Natalya V. Gorodnova (Статистика и экономика, 2016)
In difﬁcult conditions of ﬁ nancial crisis and economic sanctions, the problem ofﬁnding ways to optimize transaction costsof investment projects of public-privatepartnership has recently acquired evengreater. The result of this research is to clarify the methodology for the assessment of transactional and transformational component in the activities of companiesimplementing public investment project,ensuring complete and accurate information.